2014
DOI: 10.4049/jimmunol.1303167
|View full text |Cite
|
Sign up to set email alerts
|

Specific Microbiota-Induced Intestinal Th17 Differentiation Requires MHC Class II but Not GALT and Mesenteric Lymph Nodes

Abstract: Interleukin (IL)-17 expressing CD4+ T lymphocytes (Th17 cells) naturally reside in the intestine where specific cytokines and microbiota, such as segmented filamentous bacteria (SFB), promote their differentiation. Intestinal Th17 cells are believed to initially differentiate in the GALT and/or mesenteric lymph nodes (mLN) upon antigen encounter and subsequently home to the lamina propria (LP) where they mediate effector functions. However, whether GALT and/or mLN are required for intestinal Th17 differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…The majority of these cells are specific for SFB-derived antigens, although there are conflicting data regarding whether recognition of cognate antigen is required for their differentiation (80)(81)(82)(83). SFB colonization also induces development of secondary and tertiary lymphoid structures in the intestine, and the development of SFB-specific Th17 cells requires such organized structures (84).…”
Section: Il-23 and Autoimmunitymentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these cells are specific for SFB-derived antigens, although there are conflicting data regarding whether recognition of cognate antigen is required for their differentiation (80)(81)(82)(83). SFB colonization also induces development of secondary and tertiary lymphoid structures in the intestine, and the development of SFB-specific Th17 cells requires such organized structures (84).…”
Section: Il-23 and Autoimmunitymentioning
confidence: 99%
“…However, several studies have suggested an important role for intestinal APCs in promoting the differentiation of microbiota-dependent intestinal Th17 cells via both antigen-dependent and -independent mechanisms (75,(79)(80)(81). Intestinal Th17 cells show a substantial degree of reactivity to SFB-derived antigens and fail to develop in the absence of MHC class II on CD11c + cells (80,81,83). ATP derived from lumenal microbes specifically induces upregulation of IL-23p19, IL-6, and TGF-β-activating integrins in a CD70 hi CD11c lo population uniquely present in the lamina propria that can support the differentiation of Th17 cells in vitro (75).…”
Section: Il-23 and Autoimmunitymentioning
confidence: 99%
“…SFB genes related to colonization and immune regulation could be important for this process, and some SFB peptides have been found to promote Th17 cell differentiation (11). Intestinal dendritic cells and major histocompatibility complex (MHC) class II cells also take part in this process (4,12), although the antigen molecules and mechanisms for initial Th17 cell differentiation are still unresolved. Mechanisms that are involved in SFB regulation of the T cell response and IgA secretion need to be investigated further.…”
mentioning
confidence: 99%
“…The T helper 17 (T h 17) cells play a potential role in protecting the pathogens and inducing inflammation and autoimmunity (25)(26)(27), whereas regulatory T cells prevent inflammation and confer immune tolerance (25,28,29). Recent studies have reported that segmented filamentous bacteria played a crucial role in inducing T h 17 cells localized in lamina propria of intestinal mucosa and lenfoid tissue (24,30). Besides, increased IL-17 secreting T cells have also been observed in newly started type-1 diabetes (31).…”
mentioning
confidence: 99%
“…In murine models with type-1 diabetes, the intestinal flora was shown to alter in favor of bacteroids in comparison to healthy controls (18,19). The modified composition of microflora apparently affects T cells especially interleukin-17 (IL-17) producing T helper (T h ) and regulatory T cells (20)(21)(22)(23)(24). The T helper 17 (T h 17) cells play a potential role in protecting the pathogens and inducing inflammation and autoimmunity (25)(26)(27), whereas regulatory T cells prevent inflammation and confer immune tolerance (25,28,29).…”
mentioning
confidence: 99%